2018
DOI: 10.1186/s13014-018-0959-4
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of CT-guided implantation of 125I seeds for recurrent malignant tumors of the head and neck assisted by 3D printing non co-planar template

Abstract: BackgroundFor the recurrence of head and neck cancer after operation and radiotherapy, the local control of radioactive seed implantation is good, and it has a certain palliative effect. This study aims to investigate the acute and late side effects of a three-dimentional printing non co-planar template (3D–PNCT) for computed tomography (CT)-guided radioactive 125I seed (RIS) implantation in recurrent cancer of the head and neck.MethodsBetween January 2016 and December 2016, forty-two patients with local recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Except for grade 2 irradiation-related myelosuppression (1 case), there were no other grade 3 or higher toxicity effects. According to the reports of Jiang et al, there were no evident toxicity effects of grade 3 or higher (35). The incidence of radiation pneumonitis with grade ≥ 2 was 7.0 to 32.0% in patients receiving EBRT therapy, while that with grade ≥ 3 was 2.6 to 18.0% according to some authorized studies (36)(37)(38).…”
Section: Discussionmentioning
confidence: 98%
“…Except for grade 2 irradiation-related myelosuppression (1 case), there were no other grade 3 or higher toxicity effects. According to the reports of Jiang et al, there were no evident toxicity effects of grade 3 or higher (35). The incidence of radiation pneumonitis with grade ≥ 2 was 7.0 to 32.0% in patients receiving EBRT therapy, while that with grade ≥ 3 was 2.6 to 18.0% according to some authorized studies (36)(37)(38).…”
Section: Discussionmentioning
confidence: 98%
“…Ji et al (9) reported that Grade 3 skin/mucosal toxicities were 7.9% and Grade 4 were 2%. A study by Jiang et al (27) specifically explored the side effects of RIS implantation in the treatment of recurrent head and neck cancer showing that 14.4% of patients had Grade 1/2 skin/mucosal toxicities and no patients suffered from Grade 3/4 skin/mucosal side effects. Conversely, the toxicities of re-EBRT to head and neck cancers seemed much more severe than RIS brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…eyes, major vessels and nerve) in head and neck region, the accuracy of I 125 RSI and post-plan dosimetry was extremely critical for patients with head and neck cancer. Individualized three dimensional-printing template (3D-PT) was developed to facilitate I 125 RSI for head and neck cancer in order to improve the accuracy, optimize post-plan dosimetry, and shorten the RSI duration [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies involving 3D-PT assisted I 125 RSI were focused on the e cacy and safety pro les, mainly including local control, survival and complications [7,[11][12][13]. As the mean entrance deviation, planned and intraoperative deviation of needle depth and angular were deemed to represent the accuracy of needle related interventions, only 2 studies involving these parameters were published to described the accuracy of 3D-PT assisted I 125 RSI for head and neck cancer [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation